2009 IEEE 9th International Conference on the Properties and Applications of Dielectric Materials 2009
DOI: 10.1109/icpadm.2009.5252266
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of packet-like space charge formation in LDPE by the addition of magnesia nanofillers

Abstract: Space charge distributions were investigated in two-layer dielectric films consisting of certain combinations of low-density polyethylene (LDPE) and its nanocomposite with magnesia nanofillers at de electric fields of 25 kV/mm and 100 kV/mm at room temperature. Space charge is formed at the interface of two different materials to maintain the continuity of current when the electric field is 25 kV/mm, while packet-like charge appears only in the LDPE at 100 kVImm. These phenomena are explained by assuming that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 12 publications
0
11
0
1
Order By: Relevance
“…The experimental results and discussions both indicate that the surface-treated graphene with a content of 0.005 wt % could significantly inhibit space charge injection and accumulation in LDPE. As concluded in the references [ 12 , 13 , 14 , 15 , 16 ], for the traditional inorganic nanoparticles, including MgO, SiO 2 , ZnO, the optimum content is in the range of 0.5~5 wt % for the modification of space charge behaviors. Owing to the advantage of two-dimensional structure and an enormous specific surface area shown in Figure 2 b, graphene with a content of only 0.005 wt % could introduce a large number of microscopic interfaces between graphene fillers and LDPE polymer, which has great potential applications for the DC electronic devices and power equipment insulation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The experimental results and discussions both indicate that the surface-treated graphene with a content of 0.005 wt % could significantly inhibit space charge injection and accumulation in LDPE. As concluded in the references [ 12 , 13 , 14 , 15 , 16 ], for the traditional inorganic nanoparticles, including MgO, SiO 2 , ZnO, the optimum content is in the range of 0.5~5 wt % for the modification of space charge behaviors. Owing to the advantage of two-dimensional structure and an enormous specific surface area shown in Figure 2 b, graphene with a content of only 0.005 wt % could introduce a large number of microscopic interfaces between graphene fillers and LDPE polymer, which has great potential applications for the DC electronic devices and power equipment insulation.…”
Section: Discussionmentioning
confidence: 99%
“…Nanodielectric insulation has been one of the research hotspots to develop the advanced polymeric insulation, especially for the PE-based insulation of high-voltage direct-current (HVDC) extruded cable [ 9 , 10 , 11 ]. As early as 2005, Y. Ohki et al found that LDPE and XLPE modified by inorganic oxide nanoparticles has a much higher breakdown strength, lower conductivity, and less space charge accumulation than undoped polymer [ 12 , 13 ]. The inorganic nanoparticles, including magnesium oxide (MgO), silica (SiO 2 ), zinc oxide (ZnO) etc., are considered to be optimal additives for HVDC cable insulation [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Por otra parte, existen modelos que explican cómo se propagan estos paquetes en polímeros (Daomin et al, 2013) (Chouikhi et al, 2013). Para disminuir los paquetes de carga de espacio a través del volumen del material se han añadido nanopartículas dieléctricas al polietileno (Ohki, et al, 2009). Otros trabajos han tenido en cuenta las condiciones de preparación de las muestras ya que también la morfología influye sobre la formación de estos paquetes (Yuanxiang, et al, 2009).…”
Section: Figura 2 Elementos Que Componen Los Cables De Media Tensiónunclassified
“…IN recent years, academic research has focused on nanoparticle surface modified dielectrics [1][2][3][4][5][6], with the intention to promote insulation performance by increasing breakdown strength, dielectric polarization, suppressing space charge injection and controlling of dissipation [7][8][9][10][11][12][13]. Meanwhile, more stringent requirements from the power industry require reliable, compact and high performance solid insulation suitable for high voltage DC environments.…”
Section: Introductionmentioning
confidence: 99%